United network for organ sharing outcomes after heart transplantation for al compared to ATTR cardiac amyloidosis. Issue 10 (24th July 2020) - Griffin, Jan M.; Chiu, Leonard; Axsom, Kelly M.; Bijou, Rachel; Clerkin, Kevin J.; Colombo, Paolo; Cuomo, Margaret O.; De Los Santos, Jeffeny; Fried, Justin A.; Goldsmith, Jeff; Habal, Marlena; Haythe, Jennifer; et al.
Abstract: Light‐chain (AL) cardiac amyloidosis (CA) has a worse prognosis than transthyretin (ATTR) CA. In this single‐center study, we compared post‐heart transplant (OHT, orthotopic heart transplantation) survival for AL and ATTR amyloidosis, hypothesizing that these differences would persist post‐OHT. Thirty‐nine patients with CA (AL, n = 18; ATTR, n = 21) and 1023 non‐amyloidosis subjects undergoing OHT were included. Cox proportional hazards modeling was used to evaluate the impact of amyloid subtype and era (early era: from 2001 to 2007; late era: from 2008 to 2018) on survival post‐OHT. Survival for non‐amyloid patients was greater than ATTR ( P = .034) and AL ( P < .001) patients in the early era. One, 3‐, and 5‐year survival rates were higher for ATTR patients than AL patients in the early era (100% vs 75%, 67% vs 50%, and 67% vs 33%, respectively, for ATTR and AL patients). Survival in the non‐amyloid cohort was 87% at 1 year, 81% at 3 years, and 76% at 5 years post‐OHT. In the late era, AL and ATTR patients had unadjusted 1‐year, 3‐year, and 5‐year survival rates of 100%, which was comparable to non‐amyloid patients (90% vs 84% vs 81%). Overall, these findings demonstrate that in the current era, differences in post‐OHT survival for AL compared to ATTR are diminishing; OHT outcomes for selected patients with CA do not differ from non‐amyloidosis patients.